Implementasi Pemenuhan Hak Pasca Mediasi di Pengadilan Agama Kota Salatiga - M. Yusuf Khummaini; Abdul Qohar; Khasan Alimuddin (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
One of the advantages of resolving disputes tharough the mediation process in court is that the likelihood of implementing the agreement is higher, so that the relationship between the disputing parties in the future is still possible to maintain well. However, this does not rule out the possibility that one of the parties does not implement the agreed peace outcome, so that the right of one of the other parties are not fulfilled and cause another dispute. This study aims to examine the fulfillment of post-mediation right at the Salatiga City Religion Court. This Reseach was conducted using qualitative method. Data was obtained from field study, and using depth iterview technique. The approach used is empirical-juridical.The implementation of post-mediation rights fulfillment at the Salatiga City Religion Court has been well implemented, especially in cases that are entirely succesfull and are revoked or get a stipulation from the court as a deed of peace. However, in cases that are only partially successfull in the mediation process, it gas not been well implemented.